The Principal's Leadership in Improving Human Resource Management to Achieve Quality Islamic Educational Institutions - Diana Rahmayanti; Hinggil Permana (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The purpose of this study was to analyze the leadership of school principals in improving human resource management in order to create quality Islamic educational institutions. The research method used is a qualitative method with a library research approach by collecting books, journals, and previous research results that support the research theme, including literature on leadership which includes the leadership role of school principals, improvement of human resources, and quality Islamic educational institutions. The results of this study indicate that the principal's leadership is the most important and urgent variable in improving quality human resources and Islamic educational institutions. Improving the quality of good human resources needs to be carried out by school principals through existing activities in management functions, namely by carrying out planning, organizing, directing, and supervising all tasks that have been given to all school members, so that it will produce a good performance. and will be able to realize the vision, mission, and goals of Islamic educational institutions. For this reason, for the sake of improving its quality, Islamic educational institutions need to be assisted, defended and fought for in order to be able to live and develop in this modern era.